An Existential Dialogue between Fang Yuan and Bai Ning Bing in Novel Reverend Insanity: A Heideggerian Perspective - Anam, Rifqi Khairul (Gerakan Indonesia Kita, 2025)
This paper delves into the existential dialogue between Fang Yuan and Bai Ning Bing, two central characters in the xianxia novel Reverend Insanity. Through Heideggerian lens, researcher examine understanding of existence, mortality, and the pursuit of meaning. Fang Yuan, a seasoned cultivator, embodies a mature understanding of Being-in-the-world, accepting death and living authentically. In contrast, Bai Ning Bing grapples with his own mortality and seeks a path to meaning. By analyzing their dialogue, researcher explore themes of freedom, authenticity, and the role of the other in shaping individual identity. This paper argues that the dialogue between these two characters offers a profound exploration of the human condition and the challenges of finding meaning in the world.